Milk of Cow and Goat, Immunized by Recombinant Protein Vaccine ZF-UZ-VAC2001(Zifivax), Contains Neutralizing Antibodies Against SARS-CoV-2 and Remains Active After Standard Milk Pasteurization - Garib, Victoria; Katsamaki, Stefani; Turdikulova, Shahlo; Levitskaya, Yuliya; Zahidova, Nodira; Bus, Galina; Karamova, Kristina; Rakhmedova, Manona; Magbulova, Nigora; Bruhov, Alexander; Garib, Firuz Y.; Abdurakhmonov, Ibrokhim Y. (Frontiers in Nutrition, 2022)
Here we present the first experimental validation of the possibility for obtaining immune milk with neutralizing antibodies against SARS-CoV-2 from vaccinated cows and goat using approved recombinant protein human coronavirus vaccine in the Republic of Uzbekistan, ZF-UZ-VAC2001. In the period of two weeks after first vaccination, we detected the neutralizing antibodies against coronavirus in the blood serum of vaccinated animals. The neutralizing activity, in its peak on the 21st days after receiving the third dose (77th day from first dose), was effective in Neutralization Test using a live SARS-CoV-2 in Vero E6 cells, even after 120-fold serum titration. Colostrum of the first day after 3rd dose vaccinated cows after calving had a greater activity to neutralize the SARS-CoV-2 compared to colostrum of subsequent three days (4.080 µg/ml vs 2.106, 1.960 and 1.126 µg/ml), goat milk (1,486 µg/ml), and cow milk (0.222 µg/ml) in MAGLUMI® SARS-CoV-2 neutralizing antibody competitive chemiluminescence immunoassay. We observed a positive correlation of receptor-binding domain (RBD)-specific IgG antibodies between the serum of actively immunized cow and milk-feeding calf during the entire course of vaccination (r = 0.95, p = 0.05). We showed an optimal regime for immune milk pasteurization at 62.5°C for 30 min, which retained specific neutralizing activity to SARS-CoV-2, potentially useful for passive immunization against coronavirus infection threats as an additive approach to the vaccination. This strategy, as a supportive approach to the vaccination, could also be applicable for directly reducing the effect of COVID-19 infection in gastrointestinal tract, supporting mucosal immunity.